GOOD FENCES MAKE GOOD NEIGHBOURS: CHALLENGES AND OPPORTUNITIES IN FINALISING MARITIME BOUNDARY DELIMITATION IN THE MALACCA STRAIT BETWEEN INDONESIA AND MALAYSIA - Arsana, I Made Andi (Indonesian Journal of International Law, 2014)
Maritime boundary issues are by no mean new for Indonesia and Malaysia. Notwithstanding the fact that Indonesia and Malaysia signed a maritime boundary agreement as early as 1969, the two States have yet to finalise various pending maritime boundaries between them. Compelling cases such as Ambalat Block dispute (2005, 2009), Tanjung Berakit incident (2010) another incidence in the Malacca Strait (April 2011) and others maritime boundary issues are apparently consequences of unfinished maritime boundaries between Indonesia and Malaysia. This paper seeks to analyse challenges and opportunities in finalising maritime boundaries in the Malacca Strait between Indonesia and Malaysia. It focuses on description of maritime boundaries between the two States, followed by recent developments in the Malacca Strait. An incident involving Indonesian patrolling officers and Malaysian-flagged fishing vessels which occurred on 7 April 2011 is the key case discussed. It is viewed as a relevant representation of what happen between Indonesia and Malaysia, which also applies to other areas where maritime boundaries are pending or absent. This discussion eventually highlights the importance of maritime boundary delimitation in the Malacca Strait between Indonesia and Malaysia. Options for maritime delimitation between Indonesia and Malaysia in the Malacca Strait are the main outcomes of this paper. This is achieved by taking into consideration principle of the law of the sea, relevant jurisprudence, and existing agreement between Indonesia and Malaysia. To accurately generate options for delimitation, geospatial approach was employed by utilising relevant geospatial data and technical tools and operations.